The Impact of Tourism upon Natural Capital - Gabriela Cornelia Piciu; Carmen Trica (EIRP Proceedings, 2011)
Tourism now represents a major management problem to be faced by those who are responsible for theprotection and control the host areas and their facilities. We have identified impacts from tourist-relatedtransportation, tourist-related development, tourist activities including some recreational activities such as boating,and direct impacts of the lodging and cruise industries. Although this discussion focuses on environmental impacts.After we analyze the influence that providers of tourism services can have on their suppliers as well as the tourist.Although environmental awareness has had an important impact on the tourism industry, economic motives are stillprimary. Therefore, educational programs aimed at tourism service providers should emphasize the potentialeconomic and marketing benefits of environmental stewardship. Educational efforts to promote environmentallyresponsible tourism should be framed in accordance with the targeted audience. Tourists may be more receptive toeducational initiatives that focus on the environmental benefits of altering their behavior, while industry sectors aremore likely to be responsive to educational efforts that emphasize cost savings and an improved public image.